2020
DOI: 10.1093/burnst/tkaa026
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and accurate detection of carbapenem-resistance gene by isothermal amplification in Acinetobacter baumannii

Abstract: Background Acinetobacter baumannii (A. baumannii) is one of the pivotal pathogens responsible for nosocomial infections, especially in patients with low immune response, and infection with carbapenem-resistant A. baumannii has been increasing in recent years. Rapid and accurate detection of carbapenem-resistance genes in A. baumannii could be of immense help to clinical staff. Methods In this study, a 15-μL reaction system fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…established a 15 µl RPA reaction system to detect carbapenem-resistance genes blaoxa-23 of Acinetobacter baumannii. The test results showed that 90% of the strains showed positive amplification signals, and only 10% of the strains showed negative amplification signals, which was consistent with the results of the PCR ( Liu et al., 2020 ). Methicillin-resistant staphylococci (MRS) was a common drug-resistant strain in the clinic.…”
Section: The Application Of Rpasupporting
confidence: 84%
“…established a 15 µl RPA reaction system to detect carbapenem-resistance genes blaoxa-23 of Acinetobacter baumannii. The test results showed that 90% of the strains showed positive amplification signals, and only 10% of the strains showed negative amplification signals, which was consistent with the results of the PCR ( Liu et al., 2020 ). Methicillin-resistant staphylococci (MRS) was a common drug-resistant strain in the clinic.…”
Section: The Application Of Rpasupporting
confidence: 84%
“…baumannii and 10 1 CFU for CRAB. This sensitivity was the same as that of the real-time RPA method, which was in the range of 10 0 –10 1 CFU per reaction ( Liu et al., 2020 ). In addition, the RPA-LFS assay for detection of CRAB was simple and fast, as detection can be completed within 40 min (30 min for amplification and 10 min for LFS analysis).…”
Section: Discussionmentioning
confidence: 79%
“…During the recent period, several studies have proven the exceptionally high capability of RPA for selectively recognizing microorganisms and genes of interest. This capacity has exposed RPA as a valuable POCT technique in clinical microbiology research ( 35 40 ). Several writers have previously proven the possibility of RPA or RPA incorporating various aptamer technologies, such as multicomponent nucleic acid enzymes (MNAzymes)-based techniques and CRISPR/Cas-based techniques ( 41 , 42 ), for the identification of AMR S. aureus strains.…”
Section: Discussionmentioning
confidence: 99%